Capecitabine monotherapy in patients with metastatic breast cancer – single site experience and literature review - Załuska, Joanna; Prochowska, Ewa; Karczewska-Dzionk, Aldona; Załuski, Jerzy; Wysocki, Piotr J. (Contemporary Oncology/Współczesna Onkologia, 2008)
Breast cancer (BC) is the most frequently diagnosed malignancy in women. In Poland, in 2005 13,000 new cases and 5,000 deaths due to BC were reported. The 5-year survival rate in metastatic BC (mBC) is 25%. Chemo-therapy, which is based on various combined regimens or single-agent therapies, remains the main modality in the treatment of mBC. It is generally accepted that in case of non-rapidly progressing or non life-threatening mBC therapy should be based on single-agent strategies. Single-agent chemotherapy in comparison to polychemotherapy is less toxic but still demonstrates a significant anti-tumour activity. One of the popular drugs commonly used for monotherapy of mBC is capecitabine, a precursor of 5-fluorouracil. In the following article we present our experience with single-agent capecitabine in 82 mBC patients treated in the Department of Chemotherapy at the Great Poland Cancer Centre in Poznan, Poland. The objective response rate was 12%. Capecitabine was well tolerated and relatively rare adverse events >G2 were manageable by symptomatic treatment and dose reduction. In general, the clinical efficacy of capecitabine as well as the overall and progression-free survival times observed in our group of mBC patients were similar to those reported in the literature.